STRATEGI GURU DALAM MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN DAN KARAKTER GEMAR MEMBACA SISWA DENGAN PEMBELAJARAN PjBL DI SEKOLAH DASAR - Murdiani, Putri Setya Ayu; Supriyadi, Supriyadi (Inteligensi : Jurnal Ilmu Pendidikan, 2024)
This study aims to describe teachers' strategies in improving reading skills through the implementation of PJBL in Indonesian language learning. This study uses a descriptive qualitative approach with the research subject being a grade 1 teacher at SDN Kedung Rawan II Krembung. The data collection techniques used in the research are observation, interviews, and documentation. The data obtained is then analyzed through several stages, including data collection, data condensation, data presentation, and data verification. The results showed that teachers used eight main strategies to improve initial reading skills, including understanding reading concepts, using reading techniques, and individualized support. In addition, to improve the character of reading enthusiasts, teachers integrate innovative and creative literacy activities in the learning process. The results of this study are expected to provide practical guidance for teachers in implementing PJBL learning to develop reading skills and reading interest effectively.